2004
DOI: 10.1111/j.1537-2995.2004.03398.x
|View full text |Cite
|
Sign up to set email alerts
|

White particulate matter found in blood collection bags consist of platelets and leukocytes

Abstract: WPM originated from PLTs and WBCs. Foreign matter (e.g., plastic) was not observed in any of the units. Leukoreduction and transfusion filters can be used to remove macroscopic WPM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…[12] Swank[3] reported that high pressures were necessary to force stored whole blood through a filter and increase in pressure correlates with increase in storage time. He attributed this to formation of compact aggregates of platelets and white blood cells due to increased adhesiveness during routine storage of blood, and therefore, was responsible for increased filter occlusion.…”
Section: Pathophysiology Of Eventmentioning
confidence: 99%
See 2 more Smart Citations
“…[12] Swank[3] reported that high pressures were necessary to force stored whole blood through a filter and increase in pressure correlates with increase in storage time. He attributed this to formation of compact aggregates of platelets and white blood cells due to increased adhesiveness during routine storage of blood, and therefore, was responsible for increased filter occlusion.…”
Section: Pathophysiology Of Eventmentioning
confidence: 99%
“…Particulate matter visible to naked eye, white in color, has been described in detail by Rentas et al . [1] White particulate matter (WPM) in blood bags is reported to be composed of normal blood elements, namely aggregates of platelets, with variable amounts of fibrin and trapped red and white cells and not of extraneous material or organisms. [2]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A s documented in four papers in this issue, 1‐4 2003 was notable in transfusion medicine for the report of unexplained white particulate matter (WPM) found in red cell (RBC) components. Initially observed by the American Red Cross Southeastern region in Atlanta, Georgia, such observations spread rapidly to other parts of the country.…”
mentioning
confidence: 99%
“…As the investigations reported in this issue of TRANSFUSION indicate, WPM was predominately platelets (PLTs) with other recognized forms of cellular debris including fragments and granules from white blood cells and occasional fibrin strands 1,2 . In other words, WPM is nothing new or unexpected.…”
mentioning
confidence: 99%